Peran Live Shopping dalam Memediasi Pengaruh Social Commerce Terhadap Impulsive Buying Behavior Gen Z di Daerah Istimewa Yogyakarta - Maulana Ahnaf Fauzan; Muhammad Hamdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of Social Commerce and Live Shopping has changed digital shopping behavior patterns, especially among Generation Z consumers, through increased social interaction and real-time communication. Based on the Stimulus–Response (S–R) framework, this research aims to analyze the influence of Social Commerce on Impulsive Buying and examine the role of Live Shopping as a mediating variable for Generation Z in the Special Region of Yogyakarta. This research uses a quantitative approach through a survey of 160 respondents who actively participate in Live Shopping activities on the Shopee Live, TikTok Live and Lazada Live platforms. Data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The research results show that Social Commerce has a positive and significant effect on Live Shopping, and Live Shopping has a positive and significant effect on Impulsive Buying. However, Social Commerce does not have a direct effect on Impulsive Buying. Indirect effect testing shows that Live Shopping fully mediates the influence of Social Commerce on Impulsive Buying. This finding confirms that the social stimulus in Social Commerce is not strong enough to directly trigger impulse buying without reinforcement through interactive and real-time shopping experiences. Theoretically, this research strengthens the relevance of the Stimulus–Response framework in explaining digital consumer behavior, as well as providing practical implications for e-commerce players in designing more effective Live Shopping-based marketing strategies.